Analysis of Factor Causing The Low Interest of Student Continuing Education at SMAN 1 IV Koto Aur Malintang West Sumatra - Harisnawati Harisnawati; Sri Rahayu; Rima Sumarni (LPPM Universitas PGRI Sumatera Barat, 2019)
This research is motivated by the problem of low interest of students continuing their education to tertiary education at SMA Negeri IV Koto Aur Malintang, Padang Pariaman Regency, West Sumatra. The purpose of this study is to analyze the factors causing the low student interest in continuing education at the Higher Education. This research uses descriptive qualitative research method. The research participants were determined by purposive sampling consisting of Principals, Teachers and Grade 3 Students who did not participate the National Selection for State Higher Education Entrance (SNMPTN) in accordance with a quota of 25% (school accreditation B) of the number of grade 3 students registered for SMAN IV Koto AurMalintang, Padang Pariaman Regency. Data was collected through document studies, and interviews and then reduced, presented and concluded. The results showed that there were several factors that caused the low interest of students at SMAN IV Koto Aur Malintang Padang Pariaman in continuing their education to tertiary institutions. The first was due to economic factors, secondly the attraction of going out of the town, thirdly the lack of parental support due to the economy and low education of the parents as well as environmental factors.